The Existential-Spiritual of Development of Elderly: Thematic Review & Islamic Interpretation of al-Ashr - Oktarizal Drianus (Department of Islamic Guidance and Counseling, 2021)
This article aims to explore various literature on spiritual-existential development in the elderly. Initial exploration of this issue is considered important given the increasing structure of the aging population in Indonesia. This population, if not managed properly, will become a pathos structure. The author conducted a thematic analysis to find the main themes of spiritual development issues faced by the elderly. The analysis technique is carried out from compiling the code, determining the initial code, to creating the theme presentation and visualizing the theme. Several themes that are considered as general issues in the spiritual-existential development of the elderly, include: 1) The dynamics of spirituality which include: disconnection versus a focus on religious activities, a more honed listening ability, to a pearl of greater wisdom on the various phenomena that surround it; 2) Reflection on existential themes in the elderly, such as talk of the fate he went through, the death that would come to him, the suffering that made him strong, the struggles that made him strong, and the mistakes of the past; 3) The tasks of the spiritual-existential development of the elderly such as strengthening the belief to Allah, doing higher quality goodness (amal shaleh), mutual wills in truth and patience.